Curcuma longa and Boswellia serrata Extracts Modulate Different and Complementary Pathways on Human Chondrocytes In Vitro: Deciphering of a Transcriptomic Study - Sanchez, Christelle; Zappia, Jérémie; Lambert, Cécile; Foguenne, Jacques; Dierckxsens, Yvan; Dubuc, Jean-Emile; Delcour, Jean-Pierre; Gothot, André; Henrotin, Yves (Frontiers in Pharmacology, 2022)
Objectives: Curcuma longa (CL) and Boswellia serrata (BS) extracts are used to relieve osteoarthritis symptoms. The aim of this in vitro study was to investigate their mechanisms of action at therapeutic plasmatic concentrations on primary human osteoarthritic (OA) chondrocytes. Methods: BS (10-50 µg/mL) and CL (0.4-2 µg/mL corresponding to 1-5 µM of curcumin) were evaluated separately or in combination on primary chondrocytes isolated from 17 OA patients and cultured in alginate beads. 10 patients were used for RNA-sequencing analysis. Proteomic confirmation was performed either by immunoassays in the culture supernatant or by flow cytometry for cell surface markers after 72h of treatment. Results: Significant gene expression modifications were already observed after 6 hours of treatment at the highest dose of CL (2 µg/ml) while BS was significantly effective only after 24h of treatment whatever the concentration tested. The most over-expressed genes by CL were anti-oxidative, detoxifying, and cytoprotective genes involved in the Nrf2 pathway. Down-regulated genes were principally pro-inflammatory cytokines and chemokines. Inversely, BS anti-oxidant/detoxifying activities were related to the activation of Nrf1 and PPARα pathways. BS anti-inflammatory effects were associated with the increase of GDF15, a decrease in cholesterol cell intake and fatty acid metabolism involved genes, and a down-regulation of Toll-like receptors (TLRs) activation. As CL, BS down-regulated ADAMTS1, 5 and MMP3, 13 genes expression. The combination of both CL and BS was significantly more effective than CL or BS alone on many genes such as IL-6, CCL2, ADAMTS1, and 5. Conclusion: BS and CL have anti-oxidative, anti-inflammatory, and anti-catabolic activities suggesting a protective effect of these extracts on cartilage. Even if they share some mechanism of action, the two extracts act mainly on distinct pathways, and with different time courses, justifying their association to treat osteoarthritis.